A crystal plasticity model for porous HCP crystals in titanium alloys under multiaxial loading conditions. (1st March 2022) - Yang, Qingcheng; Ghosh, Somnath
Highlights: Crystal plasticity model for porous HCP single crystals, e.g. Ti alloys. Novel penalty-free scheme developed for maintaining specified stress-states, e.g. traxiality. Tension and compression, axisymmetric and non-axisymmetric loadings are considered. The effects of initial porosity, crystal orientation, and stress state are explored. The porous CP model is capable of modeling polycrystalline microstructures containing voids. Abstract: In this paper, an efficient and effective crystal plasticity model is proposed for porous HCP crystals subject to a variety of multiaxial loading conditions. These conditions include (i) uniaxial, biaxial, and triaxial, (ii) tension and compression, (iii) low and high triaxiality, and (iv) axisymmetric and non-axisymmetric loadings. The framework is based on a combination of variational homogenization, phenomenological extensions, and assumptions motivated by observations from the high-fidelity micromechanical analysis. A novel penalty-free algorithm is employed to reach and maintain a specified stress state while performing representative volume element (RVE)-based crystal plasticity finite element (CPFE) analysis with porosity. The RVE studies demonstrate that the initial porosity, crystallographic orientation, and stress states have a significant effect on the homogenized mechanical responses of microscopically porous RVEs. The proposed porous crystal plasticity model is developed and calibrated using a database generated from the results of micromechanical RVE analysis. The calibrated porous model is reasonably effective in predicting the response of porous crystalline RVEs.